Preliminary study to evaluate the effects of dietary bile acids on growth performance and lipid metabolism of juvenile genetically improved farmed tilapia (Oreochromis niloticus) fed plant ingredient‐based diets. (22nd January 2018) - Jiang, M.; Wen, H.; Gou, G.W.; Liu, T.L.; Lu, X.; Deng, D.F.
Abstract: A 9‐week feeding experiment was conducted to investigate the effects of dietary bile acids (BAs) on juvenile genetically improved farmed tilapia (GIFT) ( Oreochromis niloticus ) based on the evaluations of growth performance and parameters relevant to lipid metabolism. Each of five vegetable protein‐based diets containing BAs at a level of 0, 0.05, 0.15, 0.45 or 1.35 g/kg diet was fed to three replicates with 40 fish (8.2 g per fish). The results showed that weight gain (WG) increased significantly with the increase in BAs from 0 to 0.15 g/kg diet and then decreased significantly at a higher BA supplementation. Dietary BAs significantly reduced the crude lipid content in the whole body, muscle and liver tissue of GIFT. Fish fed diet with 1.35 g BAs/kg diet developed serious nuclear migration and vacuolization in hepatocytes. Gall bladder appeared to contain white solid and has fragile capsules. Dietary BA supplementation had significant effects on serum biochemical indices and activities of lipid metabolism enzymes in liver and intestine. In conclusion, dietary bile acid supplementation (0.15 g/kg) can facilitate the lipid metabolism and therefore promote the growth of tilapia. However, overdosed dietary BAs induced gallstone development, disrupted lipid metabolism and depressed the growth performances of GIFT.